Reflecții după o vizită la un cămin spital - Stanciu, Mariana (Calitatea Vieții, 1993)
For a 30 days long period, during the summer of 1991, together with a group of researchers in the field of quality of life, I visited the Hirlau Hospital, in the district of Suceava. The observations and the impressive experience I had there gave rise to the thoughts which follow.